TINJAUAN KITAB SYARAH SUNAN ABI DAWUD â€œBazdl Al-Majhud Fi Halli Aby Dawudâ€ - Rasyad, Rasyad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
This paper attempts to find one of Sunan Abi Dawud's scholarly books: "Bazdl Al-Majhud Fi Halli Aby Dawud". After a brief review of this book in various aspects it turns out that the book is a complete study of Sunan Abi Dawud than the previous books of science. This book is very important because it contains many legends of hadiths related to the law. In addition, the book of Abi Dawud is included in the group of classics of the hadith (cube cube) so there is an expression "if there is no other hadith book, the Abi Dawud is sufficient to understand the religion".